2008
DOI: 10.1002/job.541
|View full text |Cite
|
Sign up to set email alerts
|

Daily performance at work: feeling recovered in the morning as a predictor of day‐level job performance

Abstract: SummaryThis study examined the state of being recovered in the morning (i.e., feeling physically and mentally refreshed) as a predictor of daily job performance and daily compensatory effort at work. Ninety-nine employees from public service organizations completed a general survey and two daily surveys on pocket computers over the course of one workweek. Hierarchical linear modeling showed that being recovered in the morning was positively related to daily task performance, personal initiative, and organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
281
1
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(304 citation statements)
references
References 52 publications
14
281
1
8
Order By: Relevance
“…Our findings mirror the results of other studies (Binnewies et al, 2009;Fay & Sonnentag, 2002;Ohly et al, 2006), and go beyond them by demonstrating the importance of challenge appraisal. It was previously assumed that stressors such as time pressure indicate a suboptimal working condition, which needs to be acted upon, thereby making proactive behavior more likely.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings mirror the results of other studies (Binnewies et al, 2009;Fay & Sonnentag, 2002;Ohly et al, 2006), and go beyond them by demonstrating the importance of challenge appraisal. It was previously assumed that stressors such as time pressure indicate a suboptimal working condition, which needs to be acted upon, thereby making proactive behavior more likely.…”
Section: Discussionsupporting
confidence: 93%
“…Next, time pressure has consistently been found to be positively related to proactive behavior in a wide range of occupations (Binnewies, Sonnentag, & Mojza, 2009;Fay & Sonnentag, 2002;Sonnentag, 2003). One explanation for this positive relationship could be that being proactive is a way of coping with high job demands (Fay & Sonnentag, 2002).…”
Section: Introductionmentioning
confidence: 95%
“…The present studies share with others in the area (e.g., Binnewies, Sonnentag, & Mojza, 2009;Dalal et al, 2009;Foo et al, 2009;Fox et al, 2001;Tsai et al, 2007) a restriction to behaviours reported by respondents themselves. Issues of common-method variance are undoubtedly of concern in these cases.…”
Section: Other Avenues For Researchsupporting
confidence: 78%
“…Researchers interested in the examination of personal resources have increasingly utilized day-level research designs as a mechanism for understanding the dynamic nature of work (cf. Binnewies, Sonnentag, & Mojza, 2009). Day-level research designs extend COR theory by incorporating time as a boundary condition for testing theory (George & Jones, 2000;Mitchell & James, 2001), showing the daily resource investment patterns of employees and the relatively rapid fluctuation of resources within a relationship.…”
Section: Participants and Proceduresmentioning
confidence: 99%